Strategi Ramah Lingkungan: Zeolit Lokal dan Fotokatalis dalam Pengolahan Air Limbah Industri Ringan di Indonesia - Mujtahidah, miftakhun Nur (Maliki Interdisciplinary Journal, 2026)
Water pollution caused by light industrial activities a major environmental challenge in Indonesia, particularly due to the presence of metal ions, synthetic dyes, and persistent organic compounds. Although various wastewater treatment methods have been applied, many of them still face limitations in terms of efficiency and sustainability. This jurnals aims to evaluate the potential use of local zeolite and photocatalytic materials as alternative approaches for the remediation of light industrial wastewater. The study is based on a literature review of research conducted by academiscs from UIN Maulana Malik Ibrahim Malang in the field of environmental chemistry. The findings indicate that local zeolite exhibits strong adsorption performance for inorganic pollutants, especially metal ions, owing to its prous structure and high cation exchange capacity, which can be further enhanced through modification processes. Meanwhile, photocatalytic technology has demonstrated effective degradation of arganic compounds and dyes through lightdriven reactions. The integration of adsorption and photocatalysis is considered a complementary strategy that can improve treatment efficiency while minimizing secondary pollution. Overall, the utilization of local zeolite combined with the development of photocatalytic materials aligns with sustainability principles and offers promising potential for environmentally friendly wastewater management in Indonesia.